Seguimiento farmacoterapéutico en pacientes con ciática y dorsalgia atendidos en un hospital de Iquitos, 2022 - Cahuaza Salazar, Claudia Clariveth (2024)
In the research work, the objectives were to examine the sociodemographic characteristics and evaluate the impact of pharmacotherapeutic monitoring in patients with sciatica and back pain using a therapeutic adherence test (Morisky Green) with care in the neurosurgery office of Hospital III- Iquitos, EsSalud, during the months of June to November 2022. The methodology carried out was quantitative work, observational, prospective, descriptive and transversal design; The most important results were: Problem related to medications type 6 (PRM6) with 69.7% in sciatica and 75.0% back pain, the visual analogue assessment of pain (VAS) obtained intense pain 21.2% in sciatica and pain moderate 4.2% with back pain after Pharmacotherapeutic Follow-up (SFT). Therapeutic adherence was 51.5% with sciatica and back pain 68.8%. It is concluded that pharmacotherapeutic monitoring allowed improving adherence to pharmacological treatment and reducing pain in patients with sciatica and back pain treated at Hospital III-Iquitos, EsSalud, during the year 2022.